The effect of the individual organization strategy on mental hardness and the accuracy of some volleyball skills among fifth-year middle school students (Journal of the College of Basic Education, 2022)
The study aimed to prepare educational exercises for the accuracy of performing some basic skills in volleyball and employing them in the strategy of individual organization for fifth-grade middle school students, and to identify the effect of the individual organization strategy on mental hardness and the accuracy of performing some basic skills of volleyball among fifth-grade students, and the researcher adopted the experimental research approach with a design The experimental and control groups on a sample of (50) students were deliberately selected at a rate of (53.763%) from the fifth preparatory class students in Al-Mutamiziz Secondary School for Girls within the administrative formations of the Second Directorate of Education of Al-Karkh in Baghdad Governorate Continuous working hours for the school year (2019/2020), divided into each group (25 students), adopted a measure of mental rigidity and the required adjustments were made to fit the privacy of this study without removing any of its paragraphs or a change in its goals, and checking the apparent and formative honesty and consistency of it on a sample Scientific foundations, And choosing the approved accuracy tests for each of the preparation skills, defending the stadium, and overwhelming hitting. The timing of the application for learning these skills in the academic year was chosen by (3) educational units for each skill by two educational units per week according to the weekly lessons schedule, and after the end of the experiment the results were verified SPSS-V26)) for the conclusions and applications in that it helps a strategy for organizing educated singles to develop the mental hardness of educated students for the accuracy of skill performance in volleyball, and helps them to improve learning the accuracy of preparation skills, defending the stadium and overwhelming hitting with a ball For a plane, and excel by learning the accuracy of these skills over the female learners without whom they learned, it is necessary to develop the capabilities of female physical education teachers in developing the psychological factor and stimulating the role of female learners in the lesson of physical education.